A study on tapered optical fiber sensor for relative humidity measurements / Huda Adnan Abdullah Zain - Huda Adnan , Abdullah Zain (2019)
In this project, the effects of coating material which are PVA and PMMA on the tapered fiber towards relative humidity sensitivity were studied. Flame brushing was used to shape the fiber into tapered fiber. The diameters of the samples used in the experiment were in the range between 2 -10 . The power output of each sample was measured while the proposed sensor is in a locked chamber when relative humidity increased between 35-85% RH. The sensors with diameter below 4 showed good sensitivity with fine resolution. The sample of diameter 2.6 had the highest sensitivity, finest resolution and smallest standard deviation. Thus, the sample with diameter 2.6 was selected for the coating process. The PVA coated sample had the best sensitivity, linearity and resolution followed by the bare fiber and the PMMA coated sample. Next, the stability of the three samples, the bare, PVA coated and PMMA coated was tested. The power output of each sample was continuously measured in constant relative humidity inside the locked chamber. All the chambers showed good and stable performance. However, the PVA coated sample was the most consistent. Finally, the response and recovery time of the three samples was measured. Each sample was moved between two chambers with different relative humidity and the time taken for the sample to react to the abrupt change in relative humidity was measured. The PMMA coated sample had the fastest response time of the three sample. This shows that using PMMA and PVA to coat tapered fiber is a viable design choice.